(untitled) (Global Journal of Medical Research, 2018)
Post mortem time interval is still controversial point as no definitive markers estimate successful time since death even there are many studies on human or experimental models investigate physical, biochemical and molecular marker fôr identification periods of time elapsed after death. After death, no system or organ work in integrity mannar, body loss its immune defence and no elimination of breakdown of each cells which could be explain elevation of certain biochemical in serum of dead animal. In this study, we induced brain stem death induced in albino male rat and take heart blood at different time point for analysis of PH, Ast, Alt, lactate dehydrogenase, creatinine, s-fas and tnfa. It was found that PH reduced while serum lactate dehydrogenase was increased in time dependent manner. Notably, s-fas and tnfa increase in dependent manner until last time point. But AST, AlT, BUN and creatinine shown no change except little increase in last time point. On conclusion group of biochemical could be used in estimation of postmortem time interval for each time point.